ISOLASI DAN IDENTIFIKASI ZAT AKTIF EKSTRAK METANOL RIMPANG KUNYIT PUTIH (Curcuma mangga Val) FRAKSI ETIL ASETAT - Kusmiyati kusmiyati; Nurfina Aznam; Sri Handayani (Pharmaciana, 2011)
Curcuma mangga contains a lot of variety of active compound which use as traditional medicines. This research aimed to isolated and determinated the active compound of methanol extract Curcuma mangga rhizomes of ethyl acetate fraction and its rendemen. Amount of 1000 g Curcuma mangga rhizomes was macerated with methanol solvent at room temperature for 24 hours. Remaceration was done seventh times. Methanol extract was fractionated with ethyl acetate. About 39,05 g of concentrated ethyl acetate fraction was then separated by Column Chromatography. According to the similarity of UV-Vis spectra and GC-MS, active compound in methanol extract Curcuma mangga rhizomes ethyl acetate fraction is predicted as Labda-8(17),12-dien-15,16-dial with rendemen amount of 0,00149 %.